Older entrepreneurship: a literature review and research agenda. Issue 1 (31st May 2019) - Ratten, Vanessa
Abstract : Purpose: Mature age or older entrepreneurship is an understudied but important area of research due to the ageing population and changing demographics in society. The purpose of this study is to review the literature about older entrepreneurship to understand the gaps and areas that need more attention. Design/methodology/approach: A systematic literature review was undertaken and then the content was analyzed according to main themes. The key issues currently discussed about older entrepreneurship are stated, which leads to a number of future research suggestions. Findings: The findings involve the need to take more care in how to define and conceptualize older entrepreneurship and to undertake more studies that have an older sample in general entrepreneurship research. Research limitations/implications: The systematic literature review highlights the gaps in the literature about older entrepreneurs that need to be addressed in future research. Practical implications: The paper provides some suggestions about how older people can be more involved in entrepreneurship. Originality/value: This study contributes to the emerging literature about older entrepreneurship by providing an overview and directions for the future.